Formulation of Zinc Rich Coconut Nutribar Designed for Athletes - Priyadarsini, K. Anusha; Ramaswamy, Lalitha (International Coconut Community Journal, 2015)
The main dietary goal for athletes is to obtain competent nutrition to improve health, fitness and sports performance. Athletes require nutritious convenient foods like nutribars to provide instant energy and other nutrients. Zinc supplementation has been shown to increase anabolic hormone status to meet catabolic activity in athletes which is profound during training. In the current study nutribar was formulated using zinc rich food sources namely dehydrated coconut meat, cashewnuts, pumpkin seeds and cocoa. Two variations of the nutribar were prepared variation I using dark chocolate and variation II with milk chocolate. The samples were subjected to organoleptic evaluation using a 9 point Hedonic scale by semi trained panel members. The nutribars were also analyzed for selected nutrients using standardized procedures. The mean score obtained for over all acceptability was 8.0±0.632, 8.7±0.458 and 8.5±0.5 by the control, variations I and II respectively. Variations I and II had obtained a mean score of more than 8.0 for flavour and taste, while the control sample had obtained lesser scores. The zinc content of variations I and II was 7.38 mg & 5.2 mg being greater than the control.